ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN (E-COMMERCE) BERBASIS WEB DENGAN MENGGUNAKAN FRAMEWORK LARAVEL (STUDI KASUS PADA PT. GLUCKSINDO MAKMUR) - Fraderic, Daniel Ivan; Suwitno, Suwitno (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2023)
Electronic commerce or commonly known as e-commerce is a trading activity carried out by sellers and buyers to offer or buy goods or services electronically using electronic payments. With e-commerce, it will certainly facilitate transactions because sellers and buyers do not need to meet in person, and the prices offered are cheaper because sellers do not need to pay rent. With the ease of this transaction, it certainly adds to the competition in the business because the target market is wider. Competition in business is an unavoidable part, now competition in business is getting tougher in various aspects both in terms of production, service and marketing. Many companies want to develop and their products are known by the public and potential buyers, including PT. Glucksindo Makmur, which until now is still using the offline marketing system, namely sales looking for customers from one place to another to offer products. So that an electronic-based sales system is needed. The software used to design this application are PHP, MySQL, and Laravel Framework. The method used in this test is UAT. The results of this study are the presence of an E-Commerce system that can assist customers in placing orders online, knowing information on the type of product they want to buy and a clear and complete company profile. This research has succeeded in implementing the Laravel framework in designing web-based E-Commerce.